THE INFLUENCE OF SCIENCE, ENVIRONMENT, TECHNOLOGY AND SOCIETY MODELS (SETS) ON ENVIRONMENTAL LITERACY IN ELEMENTARY SCIENCE LEARNING - Siti Aliannisa Sukmiati (SPEKTRA: Jurnal Kajian Pendidikan Sains, 2025)
This research aims to determine the effect of implementing the Environment, Technology and Society Science learning model on Environmental Literacy in science learning in elementary schools. This research uses a Quasy Experimental Design and a form of research using Non-equivalent Design. The population of this study was 75 people, the research sample for class VA was 37 people and VB was 38 using a saturated sampling technique. Data collection techniques use interviews and observation. This research instrument uses multiple choice tests and questionnaires. This research data analysis technique uses tests of validity, reliability, level of difficulty, distinguishability, normality, homogeneity. Hypothesis testing uses paired sample t test and independent sample t test. Data was obtained from the average value of the pretest and posttest with the help of SPSS for Windows and Microsoft Excel software. Hypothesis testing used a paired sample t test which showed a result of 0.000 < 0.05 and an independent sample t test showed 0.010 < 0.05, so it can be concluded that there is significant influence of the application of the science, environment, technology and society learning model on environmental literacy in science learning in elementary schools.